The expert witness in Islamic courts medicine and crafts in the service of law - Shaham, Ron. (Chicago, Ill. : University of Chicago Press, 2010)
Islam's tense relationship with modernity is one of the most crucial issues of our time. Within Islamic legal systems, this struggle has played a significant role in attitudes toward expert witnesses. Shaham examines the evolution of the role of such witnesses in a number of Arab countries from the premodern period to the present.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Witnesses (Islamic law); Medical jurisprudence (Islamic law); Islamic courts; Evidence (Islamic law); Evidence, Expert; DNA fingerprinting (Islamic law); Law; Religion: general; Jurisprudence & general issues; Systems of law: Islamic law; Legal systems: courts & procedure